Dayak Benuaq Local Wisdom in the Land Use and Environmental Care efforts - Hetti Rahmawati (Jurnal Penelitian Humaniora, 2015)
This study was aimed at exploring the dynamics of wisdom in managing forest ecosystems as the basis for ecological behavior and preservation of the environment  on Benuaq Society in East Kalimantan through indigenous perspective. This study used qualitative descriptive-Explorative method. Data of this study were obtained through interviews and observations. The results show that the use of forests is based on the maintenance of balance and sustainability of forest resources as a form of harmonious relations and human responsibility to the natural environment. The local wisdom is re lected in the habits of life and the social values that lasted a long time . The value of self-transcendence, social-altruistic, and biospheric become reinforcement in ecological behavior intention to care for the forest. A form of environmental wisdom is emonstrated in the oral arts. Farming knowledge and technologies used do not harm the environment. Land use like Umaq, Simpuk, and the swelling are developed by the Benuaq conservation behavior. Customs regulations role as controller in the system of ecologically sustainable behavior in forest management